Dampak Smartphone Terhadap Akhlak Anak - Yeli Putri; Rini Rahman (Prodi Pendidikan Keagamaan Islam, 2022)
This study aims to determine the factors that can affect the morals of children in the Pratama II complex, Lubuk crocodile Padang, the positive impact of smartphones on the morals of children in the Pratama II complex, Lubuk crocodile Padang and the negative impact of smartphones on the morals of children in the Pratama II complex, Lubuk crocodile Padang. The method used in this research is qualitative with the type of field research (field research). The field research approach (field research) is a research procedure in the form of written and spoken words from predetermined informants. The results of the study show that the impact of smartphones on the morals of children in the Pratama II complex in Lubuk crocodile Padang is divided into two types, including positive impacts and negative impacts. The positive impact of smartphones is that it is beneficial for children's learning, increase children's insight, knows what is not yet known, and can be in close contact for communication and search for information. While the negative impact of smartphones is being lazy and likes to play games, making them negligent, can damage the child's personality, damaged eyes and learning to be unfocused, dependence and a tendency to look at smartphones, disobedience to parents, children's morals become impolite, children will try what is seen from the smartphone without thinking about the consequences, socializing becomes less and children's sleep hours are reduced because they stay up late while playing smartphones.